2004
DOI: 10.1093/jn/134.6.1512
|View full text |Cite
|
Sign up to set email alerts
|

A Very High 70%-Protein Diet Does Not Induce Conditioned Taste Aversion in Rats

Abstract: This study was designed to assess the effects of transition and adaptation to a very high protein diet on behavioral food responses, energy intake, body weight gain, and body composition in rats. For this purpose, adult male Wistar rats were fed either a diet with 70% of energy as protein (P70 group) or a diet with 14% of energy as protein (P14 group) for 16 d. These two groups were compared with a P14 pair-fed (P14-pf) group. A behavioral satiety sequence was also examined. The P70 group ate 21% less than the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 12 publications
0
14
0
Order By: Relevance
“…Convergent functional and anatomical evidence in rats established that the high-protein diet effect is due to an increased satiety signaling rather than a low palatability of the diet or the induction of the conditioned taste aversion (20). Although an earlier study points to an initial orosensory preabsorptive poor palatability (37), subsequent results obtained using two choices and flavor testing, behavioral satiety sequence, taste reactivity in response to different percentages or sources of proteins support that the determinant of reduced daily energy intake in rats eating a high-protein diet is a protein-specific food intake-suppressive mechanism (4,5,19,30,31). Of relevance are also choice study experiments showing that rats select a casein-containing diet (40% protein) over other proteins (46), further supporting the enhanced acceptability of casein used in the present study (50% protein from casein, 52% protein in total).…”
Section: Table 2 Fold-changes In Intestinal Hormones After 2-h Dark-mentioning
confidence: 99%
See 1 more Smart Citation
“…Convergent functional and anatomical evidence in rats established that the high-protein diet effect is due to an increased satiety signaling rather than a low palatability of the diet or the induction of the conditioned taste aversion (20). Although an earlier study points to an initial orosensory preabsorptive poor palatability (37), subsequent results obtained using two choices and flavor testing, behavioral satiety sequence, taste reactivity in response to different percentages or sources of proteins support that the determinant of reduced daily energy intake in rats eating a high-protein diet is a protein-specific food intake-suppressive mechanism (4,5,19,30,31). Of relevance are also choice study experiments showing that rats select a casein-containing diet (40% protein) over other proteins (46), further supporting the enhanced acceptability of casein used in the present study (50% protein from casein, 52% protein in total).…”
Section: Table 2 Fold-changes In Intestinal Hormones After 2-h Dark-mentioning
confidence: 99%
“…The total area under the curve (42) (11). Blood was obtained by tail prick before and at 15,30,60,120,180, and 240 min postinjection, and blood glucose was assessed using standard glucose test strips (One-Touch Ultra). The area under the curve was calculated as described above.…”
Section: Measurementsmentioning
confidence: 99%
“…47 However, the depressant effect of a high-protein diet was not abolished after vagotomy in the rat. 48 Moreover, the relevance and physiological significance of intestinal gluconeogenesis remains a subject of debate. 49 Firstly, the expression of the genes encoding PEPCK and G6Pase is very low in the intestine and only represents 0.5 and 6.5% of the mRNA abundance found in the liver, respectively.…”
Section: Gluconeogenesismentioning
confidence: 99%
“…Others have demonstrated that rats do not develop an aversion the high protein diets [20,21]. Because previos examinations of high protein diets and aversion tested aversion to diets from which the protein source was different than that used in our diets, we employed a conditioned taste aversion (CTA) paradigm and a two-diet choice test.…”
Section: Diet Aversion and Preference Testingmentioning
confidence: 99%